APLIKASI PEMIKIRAN KRITIS SEMASA PEMBELAJARAN BERASASKAN PROJEK PENDIDIKAN SENI VISUAL DALAM KALANGAN GURU PELATIH - Aziz, Ardiana; Siraj, Saedah; Darusalam, Ghazali; Ladin, Che Aleha (JURNAL MELAYU SEDUNIA, 2019)
Thinking is a process of building knowledge and understanding that involves mental activity in the human brain. There are three stages of thinking - concrete thinking followed by critical and creative. Critical thinking involves the practice of logical, accurate and chronological prediction. Although critical thinking is not taught as a subject, its elements do need to be integrated into PSV excellence. The purpose of this study was to identify the critical thinking ability level and application of critical thinking elements in solving PSV learning problems. This study is a survey study that used questionnaire instruments as a method of data collection. A total of 73 PSV trainee teachers from the International Institute of Teacher Education (IPGKBA) were involved. Data were analyzed descriptively using mean scores. The findings show that the critical thinking ability level practiced by the trainee teacher is high level with a mean of 3.99. The findings also show that the overall average of all critical thinking elements applied in solving PSV problems are all at a high level with the problem-solving skills with the highest mean (4.23) and decision-making skills with the lowest mean values (4.15). Therefore, PSV trainees should be given exposure to problem solving activities that involve authentic thinking in order to help improve their quality of thinking.